Mapping gender in ancient religious discourses - Penner, Todd C.; Vander Stichele, Caroline (Biblical interpretation series ;, 2007)
Contains essays on issues related to gender at the intersection of religious discourses in antiquity. Analyzing an array of traditions, this work aims to contribute to the goal of showing the options available for examining the interconnection of gender, rhetoric, power and ideology, as they relate to identity formation in the ancient world.